Low-energy spectrum and dynamics of the weakly interacting Bose gas - Boßmann, Lea (Journal of Mathematical Physics, 2022)
We consider a gas of N bosons with interactions in the mean-field scaling regime. We review the proof of an asymptotic expansion of its low-energy spectrum, eigenstates, and dynamics, which provides corrections to Bogoliubov theory to all orders in 1/N. This is based on joint works with Petrat, Pickl, Seiringer, and Soffer. In addition, we derive a full asymptotic expansion of the ground state one-body reduced density matrix.
CRIS-Team Scopus Importer:2024-10-02